F1FO ATP synthase molecular motor mechanisms - Frasch, Wayne D.; Bukhari, Zain A.; Yanagisawa, Seiga (Frontiers in Microbiology, 2022)
The F-ATP synthase, consisting of F1 and F¬O motors connected by a central rotor and the stators, is the enzyme responsible for synthesizing the majority of ATP in all organisms. The F1 (αβ)3 ring stator contains three catalytic sites. Single-molecule F¬1 rotation studies revealed that ATP hydrolysis at each catalytic site (0°) precedes a power-stroke that rotates subunit-γ 120°, with angular velocities that vary with rotational position. Catalytic site conformations vary relative to subunit-γ position (βE, empty; βD, ADP bound; βT, ATP-bound). During a power stroke, βE binds ATP (0°-60°) and βD releases ADP (60°-120°). Årrhenius analysis of the power stroke revealed that elastic energy powers rotation via unwinding the γ-subunit coiled-coil. Energy from ATP binding at 34° closes βE upon subunit-γ to drive rotation to 120° and forcing the subunit-γ to exchange its tether from βE to βD, which changes catalytic site conformations. In F1FO, the membrane-bound FO complex contains a ring of c-subunits that is attached to subunit-γ. This c-ring rotates relative to the subunit-a stator in response to transmembrane proton flow driven by a pH gradient, which drives subunit-γ rotation in the opposite direction to force ATP synthesis in F1. Single-molecule studies of F1FO embedded in lipid bilayer nanodiscs showed that the c-ring transiently stopped F1-ATPase-driven rotation every 36° (at each c-subunit in the c10-ring of E. coli F1FO) and was able to rotate 11° in the direction of ATP synthesis. Protonation and deprotonation of the conserved carboxyl group on each c-subunit is facilitated by separate groups of subunit-a residues, which were determined to have different pKa’s. Mutations of any of any residue from either group changed both pKa values, which changed the occurrence of the 11° rotation proportionately. This supports a Grotthuss mechanism for proton translocation and indicates that proton translocation occurs during the 11° steps. This is consistent with a mechanism in which each 36° of rotation the c-ring during ATP synthesis involves a proton translocation-dependent 11° rotation of the c-ring followed by a 25° rotation driven by electrostatic interaction of the negatively charged unprotonated carboxyl group to the positively charged essential arginine in subunit-a.